2017
DOI: 10.5812/semj.14066
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Unwanted Pregnancy with Mother and Father Attachment to Infant

Abstract: Background and Objectives: Parents' attachment is a strong and fundamental indicator in the formation of infant secure attachment and provides a model for the present-future emotional-social functioning. Since the unwanted pregnancy has harmful consequences for the health of the mother and the child and can affect the attachment of the parent to infant, this study was to determine the relationship between unwanted pregnancy and parental attachment in Ahvaz city. Methods: The sample consisted of 320 couple (320… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In the current study, men expressed concern about 'feeling depressed' and 'needing therapy', while other men disclosed diagnoses and recommended their peers seek 'professional help'. Although scarce prior research has explored whether men's fertility desires are related to father-infant bond (Sayahi et al, 2017), our finding suggest that men do express concern regarding their lack of perceived bond with baby. Alternatively, what men might be describing is a paternal-infant bond that is developing more slowly over time, facilitated by ongoing interactions with the infant (Goodman, 2005).…”
Section: Men's Concernsmentioning
confidence: 60%
“…In the current study, men expressed concern about 'feeling depressed' and 'needing therapy', while other men disclosed diagnoses and recommended their peers seek 'professional help'. Although scarce prior research has explored whether men's fertility desires are related to father-infant bond (Sayahi et al, 2017), our finding suggest that men do express concern regarding their lack of perceived bond with baby. Alternatively, what men might be describing is a paternal-infant bond that is developing more slowly over time, facilitated by ongoing interactions with the infant (Goodman, 2005).…”
Section: Men's Concernsmentioning
confidence: 60%
“…Bowlby also argues that a secure attachment style provides a basis for psychological adaptation actions [12]. Since the self-esteem and trust in others are from traits of individuals with secure attachment styles, it enables them to interact confidently and receive positive feedback, thereby facilitating the individual adaptation to new contexts and unexpected situations such as the unwanted pregnancy [37]. In line with the study, pregnant mothers with secure attachment styles had a positive affect that helped them to use effective and adaptive coping strategies with stressful and critical situations such as unwanted pregnancy and accept the present situations with enthusiasm and optimism [38].…”
Section: Discussionmentioning
confidence: 99%
“…Also, among reviewed researches, some studies have reported that there was a significant difference in attachment scores of mothers with wanted and unwanted pregnancy. When mothers reported wanted pregnancy, they were more likely to obtain a higher score of attachment (40).…”
Section: Discussionmentioning
confidence: 99%